SUMO2/3 modification of cyclin E contributes to the control of replication origin firing - Bonne-Andrea, Catherine (Nature Pub. Group, 2013)
The small ubiquitin-like modifier (SUMO) pathway is essential for the maintenance of genome stability. We investigated its possible involvement in the control of DNA replication during S phase by using the Xenopus cell-free system. Here we show that the SUMO pathway is critical to limit the number and, thus, the density of replication origins that are activated in early S phase. We identified cyclin E, which regulates cyclin-dependent kinase 2 (Cdk2) to trigger origin firing, as an S-phase substrate of this pathway. We show that cyclin E is dynamically and highly conjugated to SUMO2/3 on chromatin, independently of Cdk2 activity and origin activation. Moreover, cyclin E is the predominant SUMO2/3 target on chromatin in early S phase, as cyclin E depletion abolishes, while its readdition restores, the SUMO2/3 signal. Together, our data indicate that cyclin E SUMOylation is important for controlling origin firing once the cyclin E–Cdk2 complex is recruited onto replication origins.